A mathematical modeling approach to resource allocation for railroad-highway crossing safety upgrades - Konur, Dinçer; Golias, Mihalis; Darks, Brandon (My University, 2013)
State Departments of Transportation (S-DOT's) periodically allocate budget for safety upgrades at railroad-highway crossings. Efficient resource allocation is crucial for reducing accidents at railroad-highway crossings and increasing railroad as well as highway transportation safety. While a specific method is not restricted to S-DOT's, sorting type of procedures are recommended by the Federal Railroad Administration (FRA), United States Department of Transportation for the resource allocation problem. In this study, a generic mathematical model is proposed for the resource allocation problem for railroad-highway crossing safety upgrades. The proposed approach is compared to sorting based methods for safety upgrades of public at-grade railroad-highway crossings in Tennessee. The comparison shows that the proposed mathematical modeling approach is more efficient than sorting methods in reducing accidents and severity. © 2012 Published by Elsevier B.V. All rights reserved.
Keywords: Railroad-highway crossings; Safety upgrades; Resource allocation